Immunohistochemical human epidermal growth factor receptor 2 (her2) expression pattern in gastric adenocarcinomas in a Nigerian tertiary hospital (2024)
BACKGROUND AND OBJECTIVE: The demonstration of HER2 in gastric adenocarcinoma (GA) tissues by immunohistochemistry assists in deciding whether targeted therapy would optimise the treatment of GA patients who are HER2 positive. However, this has not been extensively studied in our patients hence the need for this study. METHODS: Recipient tissue microarray blocks were constructed from donor archival formalin fixed paraffin embedded gastric tumour tissue from 80 patients seen over a period of 17 years in a retrospective descriptive study. Slides cut from these blocks were stained with anti human HER2 antibody by immunohistochemistry and scored using the trastuzumab in gastric adenocarcinomas (ToGA) trial criteria. Data on age, gender, site of lesion and histological subtype of the gastric adenocarcinomas were also retrieved and reviewed. RESULTS: Eighty cases (52 males and 28 females; male to female ratio of 1.9:1), 55.65 ±13.50 years (modal age group 60-69 years), were studied. Most tumours (91.2%) involved the distal parts (pylorus, antrum and body) with a few (8.8%) involving the proximal part (cardia and fundus) of the stomach. HER2 was overexpressed in a total of 6 (7.5%) cases only. Two of seven (28.6%) proximal tumours showed HER2 positivity whereas only 4 of 73 (5.5%) of the distal tumours showed HER2 positivity. CONCLUSION: We had only a slightly lower HER2 overexpression rate than in studies from many other parts of the world. The observed overexpression was significantly higher in proximal than distally located tumours suggesting that distal tumours are less likely to respond to Trastuzumab than proximal tumours. The known association of distal gastric tumours with Helicobacter pylori infection probably provides for a possible difference in the molecular aetiopathogenesis of GAs by site of occurrence. The exact mechanisms for proximal gastric carcinogenesis remain to be more clearly elucidated. More studies, including clinical trials with larger sample sizes, are recommended to elucidate this differential expression of HER2 in gastric adenocarcinoma.